Prediction of planted seedling survival of five Mediterranean species based on initial seedling morphology - Tsakaldimi, Marianthi; Ganatsas, Petros; JACOBS, DOUGLASS F (New Forests, 2012)
Field performance can be predicted by evaluating nursery stock quality, but optimal morphological variables for use in these assessments may vary by species especially under dry Mediterranean conditions. Our objective was to identify initial seedling morphological characteristics that successfully predict ﬁeld performance of ﬁve Mediterranean species (Pinus halepensis, Quercus ilex, Quercus coccifera, Ceratonia silqua and Pistacia lentiscus). Container seedling morphology was evaluated following the nursery phase, and then seedlings were outplanted in the ﬁeld where ﬁeld survival was monitored for two successive years. Results indicate that survival can successfully be predicted from seedling initial morphological characteristics for all these species, yet not all the initial characteristics were good predictors. Survival of P. halepensis and Pist. lentiscus seedlings was positively correlated to initial seedling root-collar diameter, total dry weight and Dickson’s quality index, and can be reliably predicted by these variables. In contrast, seedling ﬁeld survival of the two Mediterranean evergreen oak species was correlated with few initial morphological attributes; initial diameter provided an accurate index to predict second-year outplanting survival for both species while height/diameter was a good survival predictor for Q. coccifera seedlings. For C. siliqua seedlings, seedlings with larger initial diameter and total biomass survive better in the ﬁeld. Thus, diameter was the common variable that accurately predicted survival for all species, which should be [5 mm for P. halepensis seedlings and[7 mm for the remaining species.
Keywords: Field performance; morphology; outplanting; Prediction models; seedling quality

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings - Pardos, M; Royo, A; Gil, L; Pardos, J A (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.67
Keywords: nursery location; outplanting; Pinus halepensis; Quercus ilex; Root growth; seedlings; shoot growth; survival (voyant)

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings - Pardos, M.; Royo, A.; Gil, L.; Pardos, J. A. (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.6710.1093/forestry/76.1.67
Keywords: nursery location; outplanting; Pinus halepensis; Quercus ilex; Root growth; seedlings; shoot growth; survival (voyant)